A Comparative Study of English and Galela Kinship Greetings and its Integration as a Theoretical Basis for Contextual English Learning - Asmiranda B Nurhamidin; Ali Adjam; Agus Supriyadi; Hamidah A Jasin; Sy Kurniaty K (Cakrawala Bahasa, 2026)
This study aims to analyze the comparison of kinship greeting in English and Galela, and its integration as a theoretical basis for contextual English learning. This study used qualitative methods with content analysis techniques. The data were obtained from various literature, including articles, journals, books, and dictionaries that discuss kinship terms in English and Galela. The data of the research were classified based on the kinship theory from Boriri & Samad (2022) and Nanda & Warms in Novintia (2025), then compared the results used the theory from Tajareh (2015). The results of the study show that English has 34 kinship terms that are divided into six kinship principles, and Galela has 34 kinship terms that are divided into seven kinship principles. Kinship in English and Galela both apply six principles, namely consanguineal, affinal, gender, generation, lineal, and collateral. Meanwhile, specific differences are found in the aspects of gender and bifurcation, where English is more individualistic and gender-based, while Galela is more seniority-based and pays close attention to both paternal and maternal lineages. These findings were then integrated into English language learning through a contextual teaching and learning approach. By comparing English kinship terms to the local Galela kinship structure, students are expected to understand the use of the target language without losing their cultural identity. It can be concluded that the integration of local kinship system such as Galela kinship vocabulary in to English learning is very important to create a more relevant, meaningful, and inclusive learning process for Galela students in North Maluku